2022
DOI: 10.3390/foods11091217
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Conditions to Improve Chlorogenic Acid Content and Antioxidant Activity of Extracts from Forced Witloof Chicory Roots

Abstract: Chlorogenic acids are major phenolic constituents in many herbal medicines and exhibit various bioactivities that explain the growing interest in extracting chlorogenic acids from biomass. In this context, the present study aims to maximize 3-O-Caffeoylquinic acid (3-CQA) and 3,5-O-di-caffeoylquinic acid (3,5-diCQA) contents from forced witloof chicory roots and to analyze the extraction kinetic modelling. First, the solid–liquid ratio, ethanol concentration, extraction time and temperature were studied. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
(48 reference statements)
2
13
0
Order By: Relevance
“…For comparison, two studies found yields between 2 and 6 mg/g DM of chlorogenic acid using respectively methanol and 80% ethanol during 15 min [ 3 ]. Only [ 4 ] quantified the 3,5-diCQA in the forced chicory roots. The 3,5-diCQA extraction optimum (5.97 ± 0.30 mg/g DM ) is similar to those presented in our study afterwards (5.41 ± 0.79 mg/g DM ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For comparison, two studies found yields between 2 and 6 mg/g DM of chlorogenic acid using respectively methanol and 80% ethanol during 15 min [ 3 ]. Only [ 4 ] quantified the 3,5-diCQA in the forced chicory roots. The 3,5-diCQA extraction optimum (5.97 ± 0.30 mg/g DM ) is similar to those presented in our study afterwards (5.41 ± 0.79 mg/g DM ).…”
Section: Resultsmentioning
confidence: 99%
“…A second effect appears at relatively high temperature, namely the thermal transformation of phenolic compounds. For 3,5-diCQA, the extraction yield decreases at high temperature, mostly due to the isomerisation of 3,5-diCQA to 4,5-diCQA [ 4 ] and 3,4-diCQA (data not shown). For 5-CQA, the decrease in yield occurs at a higher temperature than for 3,5-diCQA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations